Hybrid Regimes’ Response to the COVID-19 Pandemic - Ivanna Machitidze; Yuriy Temirov (Czech Journal of International Relations, 2020)
Hybrid regimes have been largely overlooked in the scholarly discussion on the effectiveness of halting the new COVID-19 virus, not least due to the lack of conceptual clarity, as such regimes are considered as the halfway or “grey area” on the authoritarianism-to-democracy path. Hence, the present paper aims to contribute to the pool of research on the internal dynamics of hybridity through exploring the responses towards the pandemic by two stable post-Soviet hybrid regimes, namely Georgia and Ukraine. The “most similar systems” comparative research design allows us to demonstrate that the two countries’ di!erent crisis management and communication strategies explain Georgia’s relative success in halting the virus spread in comparison to Ukraine throughout the first wave. The application of Henry Hale’s “single-pyramid” and “competitive pyramid” models of patronal politics highlights the lack of competitiveness in the formal and informal governance processes in Georgia’s case, as opposed to the chaotic mode of decision-making as well as plurality of informal actors in Ukraine’s case.